Minimally-invasive neonatal surgery: laparoscopic excision of choledochal cysts in neonates - Ryu, Hyo Seon (Ann Surg Treat Res, 2019)
PURPOSE: Improvements in surgical techniques and a better understanding of the unique anesthetic requirements in neonates undergoing laparoscopy have suggested that laparoscopic surgery may be effective in newborns. This study therefore evaluated the safety and feasibility of laparoscopic excision of the cyst (LEC) in neonates. METHODS: This retrospective study included 43 neonates who underwent excision of choledochal cysts between November, 2001, and January, 2018, including 21 who underwent open excision and 22 who underwent LEC. Their perioperative and surgical outcomes were reviewed. The patients were followed up for a median 37 months (range, 3–141 months). RESULTS: Baseline characteristics did not differ significantly in the open and LEC groups. Mean intraoperative peak partial pressure of arterial CO(2) (PaCO(2)) (45.5 mmHg vs. 48.0 mmHg) and total operation time (208.3 ± 71.0 minutes vs. 235.0 ± 47.2 minutes) were similar in both groups. Parents of the patients in the LEC group provided a more positive evaluation of scar scale and greater satisfaction with wound. No patient in either group experienced any critical complications. Three patients in the open excision group required readmission for cholangitis and 2 patients had ileus. No patient in the laparoscopic excision group experienced any postoperative complications during follow-up. CONCLUSION: Despite difficulties performing laparoscopic surgery in neonates, LEC was safe and feasible when intraperitoneal peak pressure was maintained under 10 mmHg and PaCO(2) was closely monitored by a pediatric anesthesiologist. Compared with open excision, LEC provided improved cosmetic outcomes without severe complications. Prospective randomized studies with large numbers of patients are warranted.